2018
DOI: 10.2174/1871520617666170425094549
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Graphene Oxide Coated Nanotised Apigenin with Paclitaxel (GO-NA/PTX): A ROS Dependent Mitochondrial Mediated Apoptosis in Ovarian Cancer

Abstract: The combination of PTX with GO-NA produces synergistic effects in SKOV-3 cells via the modulation of pro and anti-apoptotic gene and may reduce side effects of PTX.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Furthermore, apigenin downregulated Mcl-1, disturbed mitochondria activity and induced cell death, which may be the potential mechanism via which apigenin targets malignancies. Mitochondria-modulated cell death contributes to OC and resistance to cisplatin (29). It is widely recognized that changes in Bax and Bcl-2 expression levels regulate matrix metalloproteinases (30,31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, apigenin downregulated Mcl-1, disturbed mitochondria activity and induced cell death, which may be the potential mechanism via which apigenin targets malignancies. Mitochondria-modulated cell death contributes to OC and resistance to cisplatin (29). It is widely recognized that changes in Bax and Bcl-2 expression levels regulate matrix metalloproteinases (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria-modulated cell death contributes to OC and resistance to cisplatin ( 29 ). It is widely recognized that changes in Bax and Bcl-2 expression levels regulate matrix metalloproteinases ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early Detection : A number of studies have confirmed that RNA biomarkers have important clinical implications as the early indicator of cancer . This is mostly due to the fact that during the early development of tumor cells, they release significant amounts of RNA into the blood circulation and mostly being upregulated.…”
Section: Diagnostic and Prognostic Roles Of Rnamentioning
confidence: 99%
“…This may lead to cancer development or treatment resistance [12]. The identification of death inducing miRNAs might influence the outcome of treatment therapies [13], overcome treatment resistances and help to cure cancer (CA).…”
Section: Introductionmentioning
confidence: 99%